Uncertainties and conflicts: discourse analysis of relatives of patients with COVID-19 (Research, Society and Development, 2023)
At the end of 2019, China informed the World Health Organization (WHO) of an outbreak of a new respiratory disease. In the midst of this pandemic, discursive events can be observed in the various communication and information vehicles that make up the Ceará press. The article aims to analyze the speeches of relatives of people affected by COVID-19 through the public media of the State of Ceará. This is a documentary, exploratory and qualitative research, with the analysis of speeches, published in the three largest news portals in Ceará from March 1, 2020 to June 30, 2020. the following categories emerged: search for information about the family member, the suffering of isolation and the breakdown of the grieving process. Through these categories, it was possible to analyze that there is an exclusion of family members in the care process, making them invisible, also, to guarantee the transfer of information by the health team about the family member. As well as the psychological impacts related to the pandemic and control measures, such as social isolation, can be considered risk factors for mental health and the change in the family's grieving process, when they are unable to express the suffering and elaboration of the loss. The analysis of the speeches showed the occurrence of changes in social and family relationships, which are directly related to isolation and, consequently, the absence of family participation in the health-disease process.